The Multifaceted Role of Senescence Marker Protein 30 in Health and Diseases - Mukherjee, Sudisha; Dutta, Roshan Kumar; Gupta, Rinkoo Devi (Defence Life Science Journal, 2023)
Senescence marker protein 30 (SMP30) is an age-linked marker protein, the expression of which declines with aging. SMP30 binds with calcium; however, the absence of a calcium-binding EF-hand motif makes it different from other calcium-binding proteins like calmodulin. Interestingly, previous studies have shown that it binds with other divalent metal co-factors also and catalyzes the cyclisation of L-gulonate required for the biosynthesis of ascorbate in non-primates. Remarkably, SMP30 is conserved among vertebrates indicating that it isa crucial protein performing certain physiological functions. Apparently, in primates, including humans, calcium homeostasis could be the primary function of SMP30 due to the absence of ascorbic acid biosynthesis in these species. In this review, we have discussed the expression pattern of SMP30 in various cells and tissues. SMP30 expression is modulated by different internal and external factors, which we have extensively discussed here. Subsequently, its role in calcium homeostasis, cell proliferation, apoptosis, and liver regeneration has also been explored. Further, the potentiality of SMP30 as a prophylactic agent against organophosphorus nerve agent poisoning has been elucidated due to its organophosphate hydrolysing activity as a promiscuous substrate.